Removal of ammonium and phosphate in the simulated wastewater by using coal fly ash adsorbent - Komala Affiyanti Affandi; Arseto Yekti Bagastyo (Center for Science and Technology, IAIN Surakarta, 2021)
The main composition and availability of fly ash cause this waste which has potential as an adsorbent to remove ammonium and phosphate in water. Difference of main composition will cause different removal efficiency. The purposes from this research are to determine optimal condition for removing concentration ammonium and phosphate and to determine the source of fly ash which has great potential for ammonium and phosphate removal in solution. The optimal conditions were carried out by varying pH of solution and adsorbent dosages to remove ammonium and phosphate concentrations in different initial concentrations. Optimum pH of solution in this research is 8 with range of ammonium removal efficiency 8% to 14% and 16% to 75% for removing phosphate which has condition ammonium concentration higher than phosphate. Ammonium concentration lower than phosphate will have a negative effect on the removal. Adsorbent dosage of 4.5 g is able to produce optimal removal efficiency both ammonium and phosphate. From five different sources of fly ash, Punagaya fly ash has the great potential for removal ammonium and phosphate simultaneously which has an adsorption capacity of 7.17 mg/g and 19.50 mg/g for ammonium and phosphate respectively.